دراسة تحليلية ومقارنة لأشهر خوارزميات التعمية المتناظرة (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
مع دخول الحواسيب ونظم المعلومات جميع ميادين الحياة المعاصرة، أصبح أمن المعلومات من المتطلبات الأساسية لبناء منظومة أتمتة حاسوبية (كالنظم المصرفية، والتجارة الإلكترونية، والنظم الإدارية، وغيرها)، وتعدّ خوارزميات التعمية المتناظرة النواة الأساسية لأية منظومة حماية، لذلك فإن عملية اختيار خوارزمية التعمية المتناظرة (المتماثلة) ذات السوية الأمنية العالية والأداء الأفضل مهمة صعبة، ومن هنا فقد ركزنا في بحثنا هذا على تقديم نتائج دراسة مقارنة لأهم خوارزميات التعمية المتناظرة، إذ يتناول هذا البحث دراسة تحليلية ومقارنة لأشهر خوارزميات التشفير المتماثل العالمية Rijndael، Mars، IDEA، Blowfish, ( حيث أن خوارزمية Rijndael هي المقياس الدولي الحالي للتشفير AES) وذلك من خلال مقارنات جديدة تشمل أهم النواحي النظرية والعملية التطبيقية للخوارزميات المذكورة  من حيث الأمن ومستوى الأداء، وصولاً إلى استخلاص معايير مناسبة للاستخدام في بيئات مختلفة تمنع استغلال الثغرات الأمنية. Computers and information systems involve all areas of contemporary life. Therefore, information security has become a fundamental requirement for building any network application or automation system (banking, e-commerce, and administrative systems, ERP, etc.). The asymmetric algorithms are the core of any protection system. So the selection of a good asymmetric algorithm, with high security and performance, is a difficult, but important task. This search focuses on the best known algorithms to provide an analytical and comparative study of the most important asymmetric encryption algorithms, implemented in some protocols and organizations (e.g. Rijndael-AES, Mars, IDEA, and Blowfish). The comparisons include the most important aspects of new theoretical and practical applications of the algorithms listed in order to draw the appropriate standards for use in different settings to prevent the exploitation of the security gaps. We provide a short review of each algorithm, types of attacks on symmetric algorithms, security evaluation, performance and timing comparison.